The Effect of Profitability, Institutional Ownership on Tax Avoidance Moderated by Disclosure of Good Corporate Governance (Study on Consumer Goods Industry Companies Listed in the Indonesia Stock Exchange in 2016 – 2020) - Evdi Muhammad; Yulia Efni; Elvi Rahmayanti (INTERNATIONAL JOURNAL OF ECONOMICS, BUSINESS AND APPLICATIONS, 2022)
This study aims to analyze the effect of profitability, institutional ownership on tax avoidance moderated by disclosure of good corporate governance. This study uses 24 consumer goods industrial sector companies listed on the Indonesia Stock Exchange during the 2016-2020 period as research samples. The data is collected based on the annual report as well as the company's financial statements. Partial Least Square (PLS) is used as a method to analyze the data that has been obtained. The results showed that profitability had a significant negative effect on tax avoidance. Institutional ownership has no significant effect on tax avoidance. For testing the moderating variable, it is proven that the disclosure of good corporate governance is able to moderate the relationship between profitability and tax avoidance, but the disclosure of good corporate governance is not able to moderate the relationship between institutional ownership and tax avoidance.